Candida infections in paediatrics: Results from a prospective single‐centre study in a tertiary care children's hospital. Issue 2 (29th September 2016) - Mesini, Alessio; Bandettini, Roberto; Caviglia, Ilaria; Fioredda, Francesca; Amoroso, Loredana; Faraci, Maura; Mattioli, Girolamo; Piaggio, Giorgio; Risso, Francesco M.; Moscatelli, Andrea; Loy, Anna; Castagnola, Elio
Summary: To describe the epidemiology of invasive Candida infection in a tertiary care paediatric hospital. Prospective single‐centre survey on all Candida strains isolated from normally sterile fluids and urines in the period 2005‐2015 . A total of 299 ICI were documented in 262 patients. Urinary tract infection represented the most frequent diagnosis (62%), followed by fungaemia (34%) and peritonitis (4%). Fungaemia was most frequent in children with cancer (59%) or in low birth weight neonates (61%), while urinary tract infections were more frequent in patients with urinary tract malformation. C.albicans was the most frequently isolated species (60%) compared with C . non‐ albicans, but differences were present according to the site of isolation and underlying conditions. Overall 90‐day mortality was 7%, 13% in fungaemias, 8% in peritonitis and 2% in urinary tract infections. The rates of invasive Candida infection increased during the study period. Invasive Candida infection is diagnosed with increasing frequency in children. Site of isolation and aetiology are frequently related with the presence of underlying, favouring conditions. Mortality was not negligible, especially in the presence of more invasive infections and specific underlying conditions.